Insights About the Neuroplasticity State on the Effect of Intramuscular Electrical Stimulation in Pain and Disability Associated With Chronic Myofascial Pain Syndrome (MPS): A Double-Blind, Randomized, Sham-Controlled Trial - Botelho, Leonardo; Angoleri, Letícia; Zortea, Maxciel; Deitos, Alicia; Brietzke, Aline; Torres, Iraci L. S.; Fregni, Felipe; Caumo, Wolnei (Frontiers in Human Neuroscience, 2018)
Background: There is limited evidence regarding the effects of intramuscular electrical stimulation (EIMS) on the neural mechanisms of pain and disability related to chronic Myofascial Pain Syndrome (MPS). Objectives: To provide new insights into the long-term effects of EIMS on pain and disability related to chronic MPS (primary outcomes). Also, to assess the neuroplasticity state, measured by the serum brain-derived-neurotrophic-factor (BDNF) and by the motor evoked potential (MEP) baselines, could predict the long-term effect of EIMS on disability due to MPS. Finally, to evaluate if EIMS could improve the descending pain modulatory system (DPMS), and the cortical excitability parameters indexed by transcranial magnetic stimulation (TMS) measurements. Methods: We included 24 right-handed female patients with chronic MPS, 19 to 65 years old, they were randomized to receive ten sessions of EIMS, 2Hz at the cervical paraspinal region or a sham intervention (n = 12). Results: A mixed model analysis of variance revealed that EIMS reduced daily pain scores by -73.02% [95% confidence interval (CI) =-95.28 to -52.30] and disability due to pain -43.19 (95%CI, -57.23 to -29.39) at the three month follow up. The relative risk for using analgesics was 2.95 (95% CI, 1.36 to 6.30) in the sham group. In the EIMS and sham, the change on the Numerical Pain Scale (NPS0-10) during the CPM-task was -2.04 (0.79) vs. -0.94 (1.18), respectively, (P=0.01). EIMS reduced the MEP -28.79% (-53.44 to -4.15), while it improved the DPMS and the intracortical inhibition. The long-term effect on pain and disability was fitted by the MEP before treatment [(Beta=-0.61, (-0.58 to -0.26)] and by a more significant change from pre- to post-treatment on serum BDNF) (Beta=0.67; CI95%=0.07 to 1.26). Conclusion: The EIMS effects on chronic MPS improved pain and disability due to chronic MPS and reduced the analgesic use. It is suggested that these effects are mediated by bottom-up regulation mechanisms, enhancing corticospinal inhibition. Likewise, the MEP amplitude before treatment and the changes induced by EIMS in the serum BDNF predicted its long-term clinical impact on pain and disability due to MPS.